INFLUENCE OF INTELLECTUAL CAPITAL AND CAPITAL STRUCTURE OF THE COMPANY VALUE THROUGH FINANCIAL PERFORMANCE AS AN INTERVENING VARIABLE (CASE STUDY AT MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2013-2017) - Octavia, Syari; Fathoni, Ahmad Fauzan; Efni, Yulia (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
Manufacturing industry is the industry that the largest contribution to GDP growth until 2017. Although still the largest source of the increase in GDP, the contribution of manufacturing to GDP continued to decline since 2015. However, this does not cause the stock price decline of manufacturing. Based on this phenomenon, this study aims to examine the internal factors are thought to be able to increase the value of the company. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2013-2017 as many as 144 companies with a total sample of 76 companies that obtained by purposive sampling. Then, samples were analyzed using Structural Equation Modeling results show that IC and capital structure does not directly affect the value of the company. But IC and capital structure directly affects financial performance. Thus, the financial performance is able to mediate the effects of IC and capital structure to the company's value. The better the financial performance of a company, the better is also the company's value in the eyes of investors. Keywords: Intellectual Capital, Capital Structure, Financial Performance, Company Value